2020
DOI: 10.4103/jfmpc.jfmpc_1185_19
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for undernutrition in under-five children living in a migrant populated area of South Delhi

Abstract: Introduction: Undernutrition is continuing to be a major public health problem in India. Moreover, India houses more than 30% of the world's stunted children aged under 5 years. There was a paucity of a community-based cross-sectional study on the nutrition of children aged under 5 years in urban Delhi. Therefore, we conducted this study to assess the prevalence of undernutrition and their associated factors in children aged under 5 years in urban South Delhi. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
(21 reference statements)
3
10
0
Order By: Relevance
“…Of a sample of 1,459 children under five years, over half (53.8%) were continuously breastfed from birth until their current age (months). This result was similar to the previous studies in that breastfeeding was a preventive factor for reducing childhood stunting (Dabar et al, 2020;Rathaur et al, 2018;Sari et al, 2021). In a mother's breast milk, colostrum, essential nutrients, and vitamins are already included for optimal growth and development of children.…”
Section: Discussionsupporting
confidence: 91%
“…Of a sample of 1,459 children under five years, over half (53.8%) were continuously breastfed from birth until their current age (months). This result was similar to the previous studies in that breastfeeding was a preventive factor for reducing childhood stunting (Dabar et al, 2020;Rathaur et al, 2018;Sari et al, 2021). In a mother's breast milk, colostrum, essential nutrients, and vitamins are already included for optimal growth and development of children.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted in Ghana by Boah et al, 16 showed association of father's education with wasting. A study conducted by Dabar et al, 17 in South Delhi showed that underweight and stunting was significantly associated with parent's education but not with family type. A study conducted in Jaipur, Rajasthan by Chaudhary and Agarwal, (2018) 18 showed that undernutrition was associated with family type, parent's education, and socioeconomic status.…”
Section: Discussionmentioning
confidence: 94%
“…A study conducted by Jeyakumar et al, 26 in slum areas of Pune showed that birth weight was significantly associated with undernutrition while underweight was significantly associated with immunization status and wasting was associated with colostrum given and initiation of complementary feeding. A study conducted by Dabar et al, 17 in South Delhi showed that stunting was significantly associated with exclusive breastfeeding while underweight was not significantly associated with it. A study conducted by Gautam et al, 12 in Kanpur showed that malnutrition was significantly associated with birth order.…”
Section: Discussionmentioning
confidence: 95%
“…Similar studies by Hasan et al ., Dabar et al ., and Devi et al ., have shown that children of mothers with secondary or higher education were at lower risk of childhood malnutrition when compared with children of mothers with no education. [ 16 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…As the family size increases there is division of resources (dietary resources), overcrowding, and poor care of children which increases the chances of children to suffer from undernutrition. [ 17 23 ]…”
Section: Discussionmentioning
confidence: 99%